Brexit and Universities: Toward a Reconfiguration of the European Higher Education Sector? - Courtois, Aline (International Higher Education, 2018)
The prospect of “Brexit” is causing significant anxiety across the European higher education sector, as universities brace themselves for a possible departure of the United Kingdom and a reconfiguration of the sector. Our research suggests that while the impact is expected to be uneven across the region—with some possible short-term beneficiaries—research cooperation with the United Kingdom and freedom of movement are valued by universities across the region.